The Progressivity of the Malaysian Personal Income Tax System - Yong Kuan Chen (Kajian Malaysia, 2012)
In general, Malaysia has a progressive personal income tax system in which th tax rate increases as an individual's income increases. The system is intended to provide assistance for low-income earners so as not to increase their living expenses; in contrast, high-income earners can afford to contribute more to the government's revenue. The increase in tax rate across different income levels, however, may not help to achieve income equality due to factors such as a rising marginal tax rate across income brackets, tax deductions, inflation, fluctuations in earnings, tax evasion and legal loopholes. These factors cause a more uneven distribution of income, even though the income tax system is progressive. Therefore, this study aims to confirm that such factors reduce the progressivity of personal income taxation and further suggests policies that could be used to help restore the progressivity of the income tax system. Among them are the implementation of flat tax rates and the replacement of tax deductions with tax credits.